On-line State Estimator for Three Phase Distribution Networks Displayed on Geographic Information System - Suryawati, Indri; Penangsang, Ontoseno; Suprijanto, Adi; U. P., Dimas Fajar; Syai’in, Mat (IPTEK Journal of Proceedings Series, 2014)
On line monitoring in distribution system suppose to keep the operation safe and reliable. It is connected measuring sensor that placed in nodes. To minimize great cost of sensors placement, state estimator is needed. This paper proposes online state estimator using neural network. Neural network distribution state estimation solves voltage estimation by using learning approach from power flow patterns. K-matrix distribution power flow is used as analysis method. Detailed information and position of network utility is displayed by Geographic Information System (GIS), control can easily do. NNDSE was design and test for single and three phase network. The results show that NNDSE reduce sensor almost 50%.